Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Menggunakan Adobe Flash Untuk Siswa Kelas X - Mickhael P Hutagalung; Glory Indira D Purba (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to develop and produce interactive multimedia-based mathematics learning media using Adobe Flash CS 6 software that is valid, practical, and effective. This type of research is development research which refers to the ADDIE development model. This study used research instruments, the instruments used were material validation questionnaires, media, student and teacher responses regarding practicality and regarding the effectiveness of the learning media used. This study's findings indicate that: 1) The learning media's validity score of 3.245 places it in the valid category, while the media's validity score of 3.30 places it in the very valid category. 2) In the very practical category, the practicality of learning media received a score of 3.81, and in the very practical category, student assessments received a score of 3.49. 3) Learning media have a moderate or effective effectiveness score of 0.5.